Safety monitoring in inactivated COVID-19 vaccines by clinical pharmacists from a single center in China - Hu, Min; Guo, Wei; Liu, Li; Yang, Yu; Xu, Qiling; Cheng, Fang; Zeng, Fang; Zhang, Yu (Frontiers in Immunology, 2022)
Given that the vaccine-induced adverse effects were mostly based on previous laboratory research and clinical trials, real-world data in safety of COVID-19 vaccination were lacking. This study reported the adverse events (AEs) among inactivated COVID-19 vaccine recipients. Data were collected among a total of 2808 hospital employees and their family members in Wuhan, China, with 2808 receiving the first dose of inactivated COVID-19 vaccines from two pharmaceutical companies. First dose was given between April 29th to May 13th 2021. The total of 2732 vaccinees received the second dose between May 27th to July 8th 2021. The whole process of receiving vaccine was monitored by clinical pharmacists, and the information of AEs including demographics, occurrence, types, and severity were recorded by on-line questionnaire and telephone follow-up in detail. Most of the common AEs were mild and tolerable, and the overall incidence of AEs was lower than the data from safety profile in clinical trials. Besides, the incidence of AEs in the first dose (21.30%, 598) was higher than that in the second dose (16.07%, 439). Furthermore, the first injection had more severe AEs (4, 0.14%) than the second injection (2, 0.07%). The AEs involved skin, muscle, respiratory tract, gastrointestinal tract, cardiovascular system, and other tissues and systems. The most common AE was the pain at injection site (1st dose: 10.19%, 2nd dose: 12.55%). All the vaccinees with AEs for both doses recovered fully in the end. Especially, a noteworthy fact was that some AEs might cause blood coagulation disorder and bleeding risk. Therefore, ongoing monitoring of AEs after COVID-19 vaccination is paramount for evaluating the benefits and risks of each vaccine.